Pembelajaran Adaptif Berbasis Kecerdasan Buatan untuk Meningkatkan Keterampilan Matematika pada Kelas VI di UPTD SD Negeri Gili Barat Kamal - Astuti, Puji; Kusmiyati (Citra Dharma Cindekia, 2024)
This study aims to explore the impact of using an AI-based adaptive learning application on improving the mathematics skills of sixth-grade students at UPTD SD Negeri Gili Barat, Kamal District. The research method used is quantitative with a quasi-experimental design. The subjects of the study consisted of 30 students, divided into two groups: an experimental group using the adaptive learning application and a control group following conventional learning. Data were collected through mathematics skills tests administered before and after the intervention. The results showed that the average mathematics skill score in the experimental group increased from 60 to 85, while the control group only increased from 62 to 70. Analysis using t-test revealed a significant difference between the two groups (p < 0.05). These findings highlight the effectiveness of the AI-based adaptive learning application in improving students' mathematics skills and provide positive implications for the integration of technology in elementary education.